Changes in wheelchair basketball performance indicators throughout a regular season: a pilot study - Ayán, C.; Cancela, J. M.; Fernández, B. (International Journal of Performance Analysis in Sport, 2014)
Research about how the physical fitness condition and the skill level of wheelchair basketball (WB) players evolve over an entire season is very scarce. The purpose of this study was to make a further contribution to the current area of knowledge in the field of WB by providing information regarding elite players' physical conditioning and performance skills markers after being monitored throughout a season. Twelve WB players (11 male and 1 female; average age 29.6±5.4 years) from the same elite team participated in the study. During the season, the players' fitness condition and performance skills were assessed on three testing periods by means of ten specific field-based tests. The obtained results showed that the changes observed throughout the season in the WB skills and fitness of the players who completed the three assessments were mostly trivial or small, with the exception of the passing skills, which showed a significant progressive improvement. These findings suggest that the motor skills and fitness level of elite WB players do not experience significant changes throughout a competition season, with the exception of passing skills, which seems to have room for improvement.